2007
DOI: 10.1590/s1516-35982007000300015
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de novilhas leiteiras alimentadas com polpa cítrica em substituição ao feno de capim-tifton 85

Abstract: Objetivou-se avaliar o comportamento ingestivo de novilhas leiteiras em confinamento alimentadas com polpa cítrica em substituição ao feno de capim-tifton 85 (Cynodon cactylon (L.) Pear). Utilizaram-se 28 novilhas holandesas com 12 meses de idade e peso inicial de 184 kg. Os animais foram distribuídos em delineamento em blocos casualizados com quatro tratamentos e sete blocos, sendo os animais agrupados conforme o peso médio inicial. As dietas experimentais consistiam de quatro níveis de substituição (0, 16,6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
3
6
0
11
Order By: Relevance
“…In Figure 1 we can observe that during the daily period, for all experimental treatments, the animals showed higher feeding peaks, with 25 and 30% for the periods of 06:00 to 11:00 h and 12:00 to 17:00 h, respectively, during 24 hours, which corresponded to the times of feed supply, which were precisely at 09:00 and 15:00 h. This is in agreement with the reports of Abijaoude et al (2000), who claimed that, in general, ruminants (goat, sheep and cattle) present two long feeding periods during the day, especially when kept confined. These results also corroborate Mendes Neto et al (2007), who also supplied a diet twice daily and observed that the ingestion period (75.68%) was longer during the day.…”
Section: Resultssupporting
confidence: 89%
“…In Figure 1 we can observe that during the daily period, for all experimental treatments, the animals showed higher feeding peaks, with 25 and 30% for the periods of 06:00 to 11:00 h and 12:00 to 17:00 h, respectively, during 24 hours, which corresponded to the times of feed supply, which were precisely at 09:00 and 15:00 h. This is in agreement with the reports of Abijaoude et al (2000), who claimed that, in general, ruminants (goat, sheep and cattle) present two long feeding periods during the day, especially when kept confined. These results also corroborate Mendes Neto et al (2007), who also supplied a diet twice daily and observed that the ingestion period (75.68%) was longer during the day.…”
Section: Resultssupporting
confidence: 89%
“…Likewise, several authors found no differences for number of chewing per bolus ruminated in lactating cows and heifers finished in feedlot and fed with different diets. The observed values were close to 52 chewing per bolus and 46 seconds per each ruminated bolus (MENDONçA et al, 2004;MENDES NETO et al, 2007). Those published data show that such parameters exhibit great variation depending on the various factors that can influence these variables.…”
Section: Diets Effectssupporting
confidence: 74%
“…However, it was higher than that observed by Marques et al (2003) who assessed ingestive behavior of steers for 24 hours in Panicum maximum cv IPR86 Millennium in the northwestern Paraná during the summer and found approximately 66.75% of grazing time from 6 a.m. to 6 p.m., with 310.52 minutes grazing time. Mendes Neto et al (2007) also found that the food intake was higher during the day (75.68% of feeding activity occurred between 6 a.m. and 6 p.m.).…”
Section: Resultsmentioning
confidence: 74%